Design of an innovative window-balcony building module - Kozioł, Stanisław; Samborski, Tomasz; Zbrowski, Andrzej (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2021)
The article presents the concept as well as the geometric and calculation model of an innovative window-to-balcony building module that enables a reversible room rearrangement. The module to be mounted in the building structure changes both the net internal area and the exterior (façade) appearance. The window-to-balcony module provides apartment, office, and hotel room users with a flexible solution that allows for a tightly insulated window to be automatically morphed into an open balcony extension, which makes compact interior more spacious and adds external space to it. Depending on the geometric interdependencies of the ventilation system, the window may be tightly or partly sealed, just like typical tilt and turn windows. Moreover, the window can be titled from the bottom for ventilation purposes or opened fully, in which case it transforms into a balcony. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)